Application of Supply Chain Strategy of Business Competition in Business Competition Commission Decision - Haris, Haris; Al-Fatih, Sholahuddin; Jaelani, Abdul Kadir (International Journal of Supply Chain Management, 2020)
Abstract— This paper analyzes the application of norms concerning supply chain of business competition in commission for business competition decisions. The case study in this paper is in the case of supply chain of business competition conducted by PT Forisa Nusapersada in Case Decision Number 14/ KPPU-L/2015. As a comparison, this study also compares the application of SCM in cases that are almost similar, namely the Decision of the Case KPPU Number 14/KPPU-L / 2015 with the Decision of the Case KPPU Number: 06 / KPPU-L / 2004. Differentiation strategy and agile supply chain strategy had a significant impact on the firm performance under the low uncertainty. In conclusion, the companies are supposed to use environmental uncertainty as a determinant of the perceptions in setting their strategies.